2D-titanium carbide (MXene) based selective electrochemical sensor for simultaneous detection of ascorbic acid, dopamine and uric acid. (10th May 2021) - Murugan, Nagaraj; Jerome, Rajendran; Preethika, Murugan; Sundaramurthy, Anandhakumar; Sundramoorthy, Ashok K.
Graphical abstract: Abstract: Two-dimensional (2D) titanium carbide (MXene) nanosheets exhibited excellent conductivity, flexibility, high volumetric capacity, hydrophilic surface, thermal stability, etc. So, it has been exploited in various applications. Herein, we report synthesis of mixed phase 2D MXene as a catalytic material for simultaneous detection of important biomolecules such as ascorbic acid (AA), dopamine (DA) and uric acid (UA). Crystalline structure, surface morphology and elemental composition of mixed phase titanium carbide (Ti-C- T x ) MXene ( T x = –F, −OH, or −O) nanosheets were confirmed by X-ray diffraction (XRD), Raman spectroscopy, high-resolution transmission electron microscopy (HR-TEM), high-resolution scanning electron microscopy (HR-SEM) and Energy-dispersive X-ray spectroscopy (EDS) mapping analysis. Furthermore, Ti-C- T x modified glassy carbon electrode (GCE) was prepared and its electrochemical properties are studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). It was found that Ti-C- T x modified GCE (Ti-C- T x /GCE) showed excellent electrocatalytic activity and separated oxidation peaks of important biomolecules such as AA (at 0.01 V), DA (at 0.21 V) and UA (at 0.33 V). Also, Ti-C- T x /GCE sensor is enabled their simultaneous detection in physiological pH from 100 to 1000 μM for AA, 0.5–50 μM for DA and 0.5–4 μM & 100–1500 μM for UA. The limit of detection's (LOD) was estimated as 4.6 μM, 0.06 μM and 0.075 μM for AA, DA and UA, respectively. Moreover, real sample analysis indicated that spiked AA, DA and UA can be determined accurately by Ti-C- T x /GCE with the recovery ratio in the range between 100.5%–103% in human urine samples. The proposed Ti-C- T x modified electrode exhibited good stability, selectivity and reproducibility as an electrochemical sensor for the detection of AA, DA and UA molecules.